2011
DOI: 10.1242/dev.058792
|View full text |Cite
|
Sign up to set email alerts
|

Wnt6 activates endoderm in the sea urchin gene regulatory network

Abstract: SUMMARYIn the sea urchin, entry of -catenin into the nuclei of the vegetal cells at 4th and 5th cleavages is necessary for activation of the endomesoderm gene regulatory network. Beyond that, little is known about how the embryo uses maternal information to initiate specification. Here, experiments establish that of the three maternal Wnts in the egg, Wnt6 is necessary for activation of endodermal genes in the endomesoderm GRN. A small region of the vegetal cortex is shown to be necessary for activation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 49 publications
(59 reference statements)
5
75
1
Order By: Relevance
“…Nine of the eleven Wnt genes are expressed in gastrula-stage embryos (Croce et al, 2006) and 1663 RESEARCH ARTICLE Wnt1 maintains axial patterning mRNAs for several, including wnt1, wnt5, wnt8 and wnt16 (Wikramanayake et al, 2004;Ferkowicz and Raff, 2001;Wei et al, 2009), have been shown to accumulate in posterior blastomeres during mesenchyme blastula stages. In addition, loss-of-function studies suggest that Wnt1, Wnt6, Wnt7, Wnt8 and Wnt16 all are required for endoderm specification and normal gastrulation (Sethi et al, 2012;Croce et al, 2011;Wikramanayake et al, 2004). During the course of a series of Wnt knockdown experiments, we observed a particularly interesting phenotype in Wnt1 morphants suggesting that Wnt1 could have functions in addition to those in endoderm development.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Nine of the eleven Wnt genes are expressed in gastrula-stage embryos (Croce et al, 2006) and 1663 RESEARCH ARTICLE Wnt1 maintains axial patterning mRNAs for several, including wnt1, wnt5, wnt8 and wnt16 (Wikramanayake et al, 2004;Ferkowicz and Raff, 2001;Wei et al, 2009), have been shown to accumulate in posterior blastomeres during mesenchyme blastula stages. In addition, loss-of-function studies suggest that Wnt1, Wnt6, Wnt7, Wnt8 and Wnt16 all are required for endoderm specification and normal gastrulation (Sethi et al, 2012;Croce et al, 2011;Wikramanayake et al, 2004). During the course of a series of Wnt knockdown experiments, we observed a particularly interesting phenotype in Wnt1 morphants suggesting that Wnt1 could have functions in addition to those in endoderm development.…”
Section: Introductionmentioning
confidence: 76%
“…These functions have been particularly well elucidated in the sea urchin embryo. A series of Wnt signals specifies mesoderm and endoderm at one end of the primary (animal-vegetal) axis (Logan et al, 1999;Sherwood and McClay, 1999;Wikramanayake et al, 1998;Wikramanayake et al, 2004;Croce et al, 2011) and restricts anterior neuroectoderm to the opposite end (Wei et al, 2009;Yaguchi et al, 2008;Yaguchi et al, 2006). In this way, Wnt/-catenin-dependent patterning of the primary axis is like that along the anterior-posterior (AP) axis of most bilaterians; consequently, here we refer to the primary axis of the sea urchin embryo as the AP axis.…”
Section: Introductionmentioning
confidence: 99%
“…For the studies on regeneration in several animals including rat, it was found that Wnt signaling was required for the formation and proliferation of progenitor cells of the blastema (Monga et al, 2001;Stoick-Cooper et al, 2007;Lengfeld et al, 2009). Experiments on the egg development of sea urchin have verified that Wnt6 is necessary for the activation of endodermal genes in the endomesoderm gene regulatory net- work (Croce et al, 2011). Therefore, Wnt6 is likely to play an important role in the activation of many genes to initiate intestine regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the studies on Wnt6 demonstrated that it plays the role of promoting development and regeneration (Schubert et al, 2002;Geetha-Loganathan et al, 2006). Wnt6 encodes the 1st pan-epidermal Wnt signaling molecule and promotes epithelial remodeling, myogenesis, and epithelial-mesenchymal transformation; besides, it activates endodermal genes in the endomesoderm gene regulatory network (Schubert et al, 2002;GeethaLoganathan et al, 2005GeethaLoganathan et al, , 2006Croce et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Abundant comparative evidence exists for other euechinoid taxa as well, including Lytechinus variegatus (Lv) (31)(32)(33)(34)(35)(36)(37) and Paracentrotus lividus (Pl) (38)(39)(40)(41)(42). Data from these indirectdeveloping euechinoids indicate that although these taxa diverged from one another ∼90 mya (9, 43), very little appreciable change to their developmental GRNs has accrued (44)(45)(46). Although there is evidence of minor alterations to these GRNs, such as a heterochronic shift in snail expression in Lv and Sp (22), numerous studies have made clear the striking conservation of GRN linkages in these lineages.…”
mentioning
confidence: 99%